Characterization of dental care in Piauí: Evaluation of the reference service (Research, Society and Development, 2021)
The technical quality of a service can be assessed safely and effectively, scientifically based. This study allows the user of the public health system and the professional to measure the level of usefulness of the assistance that is provided. Therefore, evaluating the dental service in a reference environment enables significant improvements for the patient and professional, being able to guide the management of services to the real needs of the population. Thus, the qualitative and quantitative work used the dental sector of the Military Police Hospital (HPM) of Teresina-PI, to collect data that enabled the characterization of the services offered in dental care, as well as records of these services in front of the community. in which it is inserted. The research was guided by analysis of patients' medical records, interviews with structured forms and guidance from a dental surgeon. In the sample of analyzed records, 64% had no main complaint or characteristics that would help in the diagnosis and treatment of the patient, in addition, 42% of the professionals confessed that they did not sign the document. The work made it possible to expand this study, compare health perceptions between patient and dentist, and possible interventions to improve care for the population.